The Canine Frustration Questionnaire—Development of a New Psychometric Tool for Measuring Frustration in Domestic Dogs (Canis familiaris) - McPeake, Kevin J.; Collins, Lisa M.; Zulch, Helen; Mills, Daniel S. (Frontiers in Veterinary Science, 2019)
Introduction Psychometric tools have been developed for the assessment of behavioural and affective traits in non-human animals. Frustration can be defined as an emotional reaction experienced after a given expectation is violated. Frustration is a negative emotional state and whilst it probably plays a key role in certain behaviour problems in dogs (e.g. aggressive behaviours), there appears to have been little attempt to scale this affective tendency. Therefore the aim of the current study was to develop a tool to assess frustration tendencies in dogs. Material and Methods An online owner survey was developed. Items covered demographics, the training/behavioural history of the dog, and 33 frustration related items scored using a 5-point Likert scale. The questionnaire was disseminated via on-line channels over a 5-month period. 2348 respondents completed the questionnaire. Of these, 273 respondents completed it a second time 6 weeks later, and a separate 276 respondents completed it a second time 1 year later. Additionally, 92 paired responses were collected where two carers completed the questionnaire independently about the same dog. Intra- and inter-rater reliabilities were assessed prior to structuring the items using principal component analysis (PCA) with a Varimax rotation. Items were retained if they loaded > 0.4 on at least one of the components extracted using the Kaiser criterion. Results Twenty-two items were deemed to be reliable enough to be used in the PCA and 21 items loaded on a biologically meaningful 5-principal component solution. There was a significant positive correlation between each principal component and the owners’ general perception of their dogs’ frustration tendencies, alongside other expected correlates. Conclusion This is the first reliable psychometric tool for the assessment of frustration in dogs – the Canine Frustration Questionnaire (CFQ). Further validation with behavioural tests and physiological measures is ongoing.